Application of Modular Algorithm for Payment Card Number Validation on Mobile Devices Using LUHN - Joshua, Ishola Oluwaseun; Idris, Abdullahi Olasunkanmi; Adebiyi, Ayodele A.; Kadri, Akeem Femi; Precious, Anyaiwe Ehiedu (2023 International Conference on Science, Engineering and Business for Sustainable Development Goals (SEB-SDG), 2023)
The Luhn algorithm is the first line of defense in many e-commerce sites and is used to validate a variety of identification numbers such as credit card numbers. Nevertheless, many card numbers exist and at such volumes, the algorithm cannot distinguish among these numbers. A variety of tests show that the Luhn algorithm suffers from weaknesses including the failure to determine the length and type of credit card number being analyzed. The study intends to enhance the Luhn algorithm for the validation of credit card numbers. Enhancement of the Luhn algorithm helped to determine the length and type of credit card number for effective single error detection, effective transposition error detection and jump transposition error detection, effective twin error and jump twin error detection, and effective phonetic error detection in credit card number generation and validation. The enhanced Luhn algorithm solved the limitations of the existing Damm and Verhoeff in the process of payment card generation and validation. The study gave a thorough understanding of how the Mod 10 checksum is used in conjunction with the Luhn Algorithm to produce a legitimate payment card. The use of this system will greatly increase security and enhance efficiency in the use and operation of payment cards. To develop this system, MasterCard and Visa credit cards were used as examples. To improve the security of data and crucial information that can be extremely valuable to the user, other sorts of connected cards might also profit from it.